Practice of bio-medical research amongst doctors in Owo - Charles O. Omolase; A.A. Egberongbe; O.O. Komolafe; A.A. Olasinde; O.A. Adeosun (South African Family Practice, 2015)
Aim: This study aimed at appraising the practice of bio-medical research amongst doctors working at Federal Medical Centre, Owo, Ondo State, Nigeria. Barriers to health research were also identified.